Análise de distorção harmônica em sistema de geração fotovoltaico conectado a rede: estudo de caso USF – Mineirão - Taniguchi, Vitor Hugo Slongo (Universidade Federal do Tocantins, 2019)
This work presents, initially, a theoretical foundation about harmonics in electrical systems, and its influence on electrical equipment, focusing on energy inverters. It also presents the limits defined by the regulatory bodies of the electric power quality standards, both national and international. The case study makes a harmonic distortion analysis within the Solar Photovoltaic Plant - Mineirão, located in the city of Belo Horizonte - MG, where the work has the main objective of observing the interaction with multiple inverters of the photovoltaic plant, due to the occurrence of attenuation or aggravation of the harmonic distortions in the installations and to compare with the norms. Thus, measurements were analyzed with several locations, directly in the inverter, in the room with several inverters, in the elevating substation and in the interconnection, which in this case is the PAC (common coupling point), with energy quality analyzers. After analysis through a software, PowerLog v.5.6 and Microsoft Excel, perform a comparison with the values shown in the standards, looking like a conclusion verifying its mitigation / attenuation of the harmonics.